IMPROVING QUALITY OF ARABIC TRANSLATION COURSE THROUGH JIGSAW COOPERATIVE LEARNING - Fitriyah, Tika; Fauzi, Moh. Fery (Arabic Education Department, Islamic Studies Faculty, University Muhammadiyah of Malang, 2020)
Translation is not only a process of language transfer, but also a transfer of culture from the source language to the target language. For this reason, translators must have broad and rich insights. The process to enrich cultural insights, knowledge, and treasures in the translation process can be formed through Jigsaw learning model because it is student-centered learning and requires them to independently seek and share knowledge. This study aimed to improve the ethos of students learning in Arabic translation subject and to improve students? Arabic translation quality. This classroom action research was conducted two cycles (repeated seven times). Each cycle referred to Spiral Model by Kemmis, McTaggart, and Nixon. The subjects were 52 students of C Class and D Class in Terjemah Arab-Indonesia Course at Arabic Language and Literature Department of UIN Sunan Kalijaga Yogyakarta. The data of students? learning ethos were obtained from performance grading rubric in Jigsaw learning and the data of Arabic translation quality were obtained from students worksheet assesment and end-of-cycle Arabic translation test. The results showed that Jigsaw improved (1) the ethos, the activeness, and the independence of students in seeking and sharing knowledge through Jigsaw and (2) the quality of Arabic-Indonesia translation. This model was effectively used for this course because students can translate longer texts with relatively short time.